Ethnoscience-Based E-Magazine Using the Scientific Critical Thinking Model to Enhance Scientific Literacy - Rusmansyah Rusmansyah; Parham Saadi; Helen Natalia Siregar; Arief Ertha Kusuma; Asmi Rusmanayanti (Yayasan Keluarga Guru Mandiri, 2026)
The importance of scientific literacy has grown significantly in this technological era; however, students' proficiency in this area remains inadequate. To address this issue, the study developed an ethnoscience-based e-magazine, utilizing the Scientific Critical Thinking (SCT) model to enhance students' comprehension of acid-base concepts. The development process followed the ADDIE model, and a preliminary trial was conducted involving 28 eleventh-grade science students from SMAN 1 Alalak. Data were collected using both test and non-test instruments, revealing that the SCT-based ethnoscience e-magazine exhibited excellent quality. The e-magazine was comprehensively validated as highly suitable, encompassing its content, presentation, language, and media design. Furthermore, it proved highly practical for use in both individual and group learning. High N-gain scores further confirmed its effectiveness in enhancing students' scientific literacy